Isothermal Modelling on the Removal of Copper Using Durvillaea antarctica (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2019)
Heavy metals pollution in the Antarctica is emerging as an important problem due to anthropogenic activities. Bioremediation of metal pollution especially copper in Antarctica in the future using biosorption is the most environmental-friendly method. Biosorption using Durvillaea antarctica, an alga that lives in the Antarctic region does not involve the introduction of new potentially foreign species. In this study, the isotherms of copper biosorption by the alga is modelled according to various models ranging from one to five parameters models such as Henry, Langmuir, Dubinin-Radushkevich, Freundlich, BET, Toth, Sips, Fritz-Schlunder IV, Baudu and Fritz-Schlunder V. All gave visually acceptable fitting with the exception of the Henry model. Statistical analysis based on root-mean-square error (RMSE), adjusted coefficient of determination (adjR2), bias factor (BF), accuracy factor (AF) and corrected AICc (Akaike Information Criterion) showed that the Sips model is the best model. The calculated Sips parameters kS value of 12.52 (95% confidence interval from 3.593 to 21.439), qmS value of 0.97 (95% confidence interval from 0.905 to 1.026) and nS value of 0.67 (95% confidence interval from 0.531 to 0.806).
Keywords: Biosorption; Durvillaea Antarctica; isotherms; copper; Sips